2019
DOI: 10.3390/ma12060881
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Properties of Wood-Plastic Composites with Different Compositions

Abstract: The thermal performance of wood–plastic composites (WPCs) with different fiber, different fiber contents, and different lubricants were investigated in this paper. The results show that the thermal degradation temperature, melting temperature, crystallization temperature, crystallinity, and viscosity of WPCs with wood fiber were slightly higher than those of WPCs with floor sanding powder and rice husk. As the wood fiber content increased, the melting temperature and crystallinity of WPCs decreased while the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…It was suggested that the addition of NCC impeded the movement of the molecular chain of the composites, thus reducing the regular arrangement. The presence of NCC caused the molecular chain to be less likely to diffuse into the crystal nucleus, and lowered the crystal growth rate that subsequently decreased the crystallinity [ 61 ]. Instead of being the sufficient nucleating agent, the surface of NCC was partially attached to the sulfate group as a by-product of the acid hydrolysis process, and limited the nucleation of the PP matrix, which decreased the crystallinity of the nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that the addition of NCC impeded the movement of the molecular chain of the composites, thus reducing the regular arrangement. The presence of NCC caused the molecular chain to be less likely to diffuse into the crystal nucleus, and lowered the crystal growth rate that subsequently decreased the crystallinity [ 61 ]. Instead of being the sufficient nucleating agent, the surface of NCC was partially attached to the sulfate group as a by-product of the acid hydrolysis process, and limited the nucleation of the PP matrix, which decreased the crystallinity of the nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…This reduction in the melting enthalpy can be correlated with the dilution effect of the SiC particles within the PBS matrix. In addition, the incorporation of SiC limits the movement of the PBS molecular chain and the released melting enthalpy is reduced, leading to changes in the crystalline properties of the PBS composites [28]. The degrees of crystallinity of the semi crystalline PBS composites were calculated using Equation (2):…”
Section: Resultsmentioning
confidence: 99%
“…This is also visible in the shape of the melting peaks presented in Figure 8c,d, where the peaks of the WPC are smaller but also rather wider than those of the nanocomposites (full thermograms can be found in Figures S3 and S4). The reason can be attributed to the significant increase in the viscosity of the polymer at such high content of reinforcements, which can restrict the movement of the polymer chains obstructing them from diffusion to the crystal nuclei [33]. However, the experimental scatter is rather high, and more specimens have to be tested to exclude possible influence of material inhomogeneity.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%